STRUCTURE, FUNCTION, AND INHERITANCE SYSTEM OF THE GAMBANG RANCAG ORAL TRADITION IN THE BETAWI COMMUNITY - Attas, Siti Gomo (LITERA, 2019)
STRUCTURE, FUNCTION, AND INHERITANCE SYSTEM OF THE GAMBANG RANCAG   ORAL TRADITION IN THE BETAWI COMMUNITYAbstractJakarta is inhabited by people formed from a melting plot process, namely mixing of various ethnicities and regions, both from within and outside Indonesia. From the melting plot process, the position of the Betawi people changed to a new identity called the Betawi tribe or the Betawi people. This aims of study is to describe the structure, function, and inheritance sistem of the gambang rancag   oral tradition in the Betawi community. This research was conducted in four areas of DKI Jakarta and another area in West Java, namely Depok. The choice of location of this research was carried out because objectively these areas were the population base of the Betawi community. Data collection by observation, interview and documentation study. Data analysis with interdisciplinary approach, structural theory in Abrams and G. L. Koster Malay poetry, Albert Lord's formula theory and inheritance sistem, and Functions by Alan Dundes and Teeuw. The results of this study were first, describing the existence of communication between the creator, the text, the audience, and the community that can be considered through the text structure (1) the flow scheme, (2) the theme, and (3) the character's actions. Second, functions, were (1) affirmation function, (2) negation function, and (3) restoration function. The third, were the inheritance sistem, includes: (1) giving the model, (2) modeling the model, and (3) showing the model.Keywords: oral tradition, gambang rancag  , structure, function, inheritance, Betawi community STRUKTUR, FUNGSI, DAN SISTEM PEWARISAN TRADISI LISAN GAMBANG RANCAG   PADA MASYARAKAT BETAWI Abstrak Jakarta didiami oleh masyarakat yang terbentuk dari proses melting plot, yaitu percampuran dari berbagai etnik dan wilayah, baik dari dalam maupun luar Indonesia. Dari proses melting plot, kedudukan orang Betawi berubah menjadi identitas baru yang dinamakan suku Betawi atau orang Betawi. Penelitian ini bertujuan mendeskripsikan struktur, fungsi, dan sistem pewarisan tradisi lisan gambang rancag   pada masyarakat Betawi. Penelitian ini dilaksanakan di empat wilayah DKI Jakarta dan satu  daerah di Jawa Barat, yaitu Depok. Pemilihan lokasi penelitian ini dilakukan karena secara objektif daerah-daerah tersebut merupakan basis penduduk masyarakat Betawi. Pengumpulan data dilakukan dengan observasi, wawancara, dan studi dokumentasi. Analisis data dilakukan dengan pendekatan interdisiplin, teori struktur puitika Melayu Abrams dan Koster, teori formula dan sistem pewarisan oleh Lord, dan fungsi oleh Dundes dan Teeuw. Adapun hasil penelitian ini, yaitu pertama, menggambarkan adanya komunikasi antara pencipta, teks, penonton, dan masyarakat yang dapat diperhatikan melalui struktur teks  (1) skema  alur, (2) tema, dan (3) lakuan tokoh. Kedua, fungsi, yaitu (1) fungsi afirmasi, (2) fungsi negasi, dan (3) fungsi restorasi. Ketiga, yaitu sistem pewarisan, meliputi: (1) memberikan model, (2) mencontoh model, dan (3) mempertunjukkan model. Kata Kunci: tradisi lisan, gambang rancag  , struktur, fungsi, pewarisan, masyarakat Betawi